Pengaruh Konflik Kerja, Kualitas Kerja dan Stress Kerja Terhadap Kinerja Karyawan di CV. Maha Surya Motor Penarukan - Luh Novi Listyawati; Riana Dewi Kartika (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia, 2024)
Performance is the result of work that can be achieved by an individual or a group within an organization, both quantitatively and qualitatively, in accordance with their authority and responsibilities, in an effort to achieve the organization's goals legally, without violating the law, and in accordance with morals and ethics. The purpose of this study is to determine the effect of work conflict, work quality, and job stress on employee performance at CV. Maha Surya Motor Penarukan. This study uses a quantitative approach. The data collection technique used in this study is a questionnaire with measurement tools tested for validity and reliability, with 42 employees of CV. Maha Surya Motor Penarukan selected as respondents.The data analysis techniques used in this study are Descriptive Statistics, Classical Assumption Tests, and Multiple Linear Regression. Based on the research results, it is shown that the work conflict variable has a positive but not very significant effect on employee performance, the work quality variable has a positive but not significant effect on employee performance, and the job stress variable has a positive and significant effect on employee performance. This study concludes that to improve employee performance at CV. Maha Surya Motor Penarukan, the company needs to manage work conflict well, enhance work quality through training and development, and reduce job stress by creating a more conducive work environment.